Microhabitat preference of the Banggai Cardinalfish (Pterapogon kauderni): a behavioural experimental approach. Issue 1 (September 2020) - Moore, A M; Yasir, I; Ambo-Rappe, R; Ndobe, S; Jompa, J
Abstract: The Banggai cardinalfish Pterapogon kauderni is an endangered endemic species with an exceptionally small native distribution and an unusual life history. A paternal mouthbrooder with direct development, symbiosis with benthic organisms (referred to as microhabitat), is crucial to its survival. This is especially so for postflexion larvae (recruits), after their release from the male parent's buccal cavity. Microhabitat preference in P. kauderni has been studied empirically based on a survey of wild populations. This study adopted an ex-situ experimental approach to P. kauderni microhabitat preference using two well established behavioural trial methods: choice flume and choice tank. The experimental animals were sourced from the introduced P. kauderni population in Palu Bay, Central Sulawesi, Indonesia. The choice flume method was applied at the Central Sulawesi Marine and Fisheries Service Hatchery in Mamboro, Palu, with microhabitats Diadema setosum and D. savignyi . The choice box method was applied at the Universitas Hasanuddin Centre for Research and Development in Makassar, South Sulawesi, Indonesia, with microhabitats Heteractis crispa, Entacmaea quadricolor, D. savignyi and D. setosum . The results indicate the most to least preferred preference hierarchy of D. savignyi, D. setosum, H. crispa, E. quadricolor . While the preference for the sea anemone H. crispa compared to E. quadricolor is consonant with empirical in situ studies on P. kauderni, the observed preference for D. savignyi over D. setosum was unexpected, and points to the need for further research. Observations made during the trials also raise the possibility that imprinting may occur and influence subsequent microhabitat preference.